Features of angina development across age groups: data from the World Health Survey (WHS) and the WHO Study on global AGEing and adult health (SAGE) - T. M. Maksimova; V. B. Belov; N. P. Lushkina (Российский кардиологический журнал, 2013)
Aim. Using the data from longitudinal studies, to identify the determinants of coronary heart disease (CHD) development. Material and methods. Using the data from the two studies (2003 and 2007), a sample of people aged 50 years and older (135 men and 336 women), who were examined both in 2003 and 2007, was selected. All participants were divided into three groups: Group I – with CHD (angina) in 2003 and 2007; Group II – with CHD (angina) in 2007 only; and Group III – with no symptoms or signs of CHD (angina) in 2003 and 2007. The main health parameters, lifestyle characteristics, and health service use were assessed and analysed. Results. Mean age of people free from CHD (angina) in 2003 was significantly lower than in those with CHD (p<0,05). In men and women from Group I, mean height values decreased by 2007, and in Group I men, there was also a statistically significant reduction in body weight (p<0,05). The highest percentage of individuals with normal body weight (body mass index 18,5–24,9) was observed in people without CHD (angina) by 2007 (60% men and 42,1% women). In Group II, this percentage was 21,4% in men and 33,2% in women (approximately 33% and 22,6%, respectively, among people with long duration of the disease). CHD developed even in people with normal or low body weight. Joint pathology, diabetes mellitus, and dental health problems were associated with the development of CHD. In Group I, there was an increase in the prevalence of sleep disturbances (31,3%). No differences in the prevalence of risk factors were observed for Groups II and III. While hospital admissions due to CHD were less frequent than in other countries, the proportion of people seeking medical help was quite large. Conclusion. In people aged 50+, age-related changes determine the development of CHD, regardless of the presence of risk factors. There is a need for more longterm prospective studies on the disease development, preventive measures, early diagnostics and adequate therapy across different contexts.